Perencanaan Produksi Crude Palm Oil (CPO) dengan Metode Goal Programing di PT. Beurata Subur Persada - Arie Saputra; Wahyudi Wahyudi (Jurnal Optimalisasi, 2021)
Production planning is the process of producing goods in a certain period in accordance with what is predicted or scheduled through organizing resources such as labor, raw materials, machinery and other equipment. PT. Beurata Subur Persada is one of the palm oil mills whose production planning and production capacity can still be optimized again, optimizing production planning will have an impact on costs and profits that have been maximized. During this time PT. BSP often experiences idle capacity and lack of raw materials due to poor initial planning. This study aims to determine the optimal amount of production planning production for production planning at PT. Beurata Subur Persada period January - December 2021. Optimization of CPO production is carried out using the Goal Programming method and model completion is carried out with the help of the Linear Interactive Discrete Optimizer (LINDO) program. The objective function of the model is based on the goals to be achieved by PT. BSP, namely meeting the demand for CPO, minimizing CPO production costs, minimizing the cost of purchasing Fresh Fruit Bunches (FFB), and maximizing FFB processing. The results obtained from this study are the number of Optimal CPO Production Planning at PT. The percentage of Subur Persada for production planning for the period January 2021 – December 2021 is 2,483,173,750 Kg in a row; 2,380,724,000 Kg ; 2,370,230,250 Kg ; 2,454,504,750 Kg ; 2,610,965750 Kg ; 2,765,000,500 Kg ; 2,934,000,500 Kg ; 3,067,094,500 Kg ; 2,983,999,500 Kg ; 2,972,001,250 Kg ; 2,836,852,500 Kg ; 2,650,128,250 Kg and the Optimal FFB Purchase Amount to be achieved by PT. Beurata Subur Persada for production planning for the January 2021 – December 2021 period, respectively, is 7,577,220,500 Kg; 7,951,500,000 Kg ; 8,673,920,000 Kg; 7,685,560,000 Kg ; 7,827,840,000 Kg ; 9,977,241,000 Kg ; 10,489,481,000 Kg ; 12,910,930,000 Kg ; 11,779,611,000 Kg ; 10,345,760,000 Kg ; 8,700,900,000 Kg and 6,983,760,000 Kg.